Motif of E-Wallet Users on Gen Z in Marketing Communications Perspective (Case Study of LinkAja Users in Purchasing Decisions) - Naufal Bagus Luthansa; Daniel Susilo (Universitas Darussalam Gontor, 2022)
The developments of the digital era are currently quite rapid, especially in the use of electronic payment applications called e-wallets. With so many e-wallet payment apps, consumers' purchasing decisions require a lengthy process. The object in this study is related to the user of LinkAja products. Consumers feel the attractive message that the product conveys, such as the message that consumers receive about the purchase decision then becomes the determining factor for consumers towards e-wallet products. Some interesting messages received by a LinkAja product convey their message to consumers. This is a crucial factor for consumers, especially Gen Z, to choose products. This research is a descriptive qualitative research with a case study method. Focus Group Discussion (FGD) data collection technique, participants consisted of ten men and women aged 18-25 years. This study aims to find out how the motives of every LinkAja consumer who uses e-wallets as practical transactions in Indonesia. Therefore, to achieve this goal, it is necessary to have a motive for LinkAja users in deciding on a purchase. Keywords: E-Wallet Users; Gen Z; Marketing Communications; LinkAja; Buying decision.